Digital Marketing Influence on Marketing Performance: The Role of Customer Engagement and Relationship Marketing - Safitri, Diana; Komaryatin, Nurul (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This research decisively establishes the influence of digital marketing on the marketing performance of Small and Medium Enterprises (SMEs) in the food sector of Jepara Regency, underscoring the critical mediating roles of customer engagement and relationship marketing. Employing a robust quantitative methodology with Structural Equation Modeling (SEM), analyzed through SmartPLS version 4.0, questionnaires were distributed to 150 SME owners in the food sector. The results indicate that while digital marketing does not directly enhance marketing performance, customer engagement and relationship marketing are vital mediators that significantly strengthen this connection. This reinforces the notion that cultivating high levels of customer engagement and fostering strong relationships are essential for maximizing the effectiveness of digital marketing strategies. Consequently, this research provides crucial insights for SMEs, highlighting the challenges inherent in digital marketing implementation and the urgent need for a comprehensive approach to elevate their marketing performance.